The agroecology power: how the environmental representation and management of leafcutting ants by peasants from Assentamento Dênis Gonçalves can be transformed - da Silva Novato, Thiago; Taboada Soldati, Gustavo; Lopes, Juliane (Ethnobiology and Conservation, 2020)
The relationship between human beings and leaf-cutting ants is secular and emerged along with the agricultural practices for food production. The environmental representation of peasants about leaf-cutting ants may be related to their country life background, implying directly on the control method used by them to reduce agricultural losses. In this context, it was investigated the relationship between the peasants' socioeconomic profile with their environmental representations about leaf-cutting ants and used control methods. Eighty families from Assentamento Dênis Gonçalves (Brazilian Landless Workers’ Movement) were interviewed, in order to socioeconomically characterize them and ask if they know the term agroecology, what are leaf-cutting ants, their ecological function and used control method. Two profiles were identified, one composed by older peasants who had never studied, did not know the term agroecology, had a negative conception about leaf-cutting ants and used commercial formicides. The second profile was constituted by peasants with the opposite characteristics of the first. Agroecology concepts and practices seem to have a high potential to change environmental representations about leaf-cutting ants and used control methods in the studied area. By comprehending the leaf-cutting ants’ role in the ecosystem a gradative transition to alternative control methods rather than the commercial ones was observed. This gradual transition enables a better relationship between ADG peasants and leaf-cutting ants. The organic compounds commonly used are clues to the urgent search for a sustainable leaf-cutting ant control method.